Bottom-up cascading effects of quarry revegetation deplete bird-mediated seed dispersal services - Sampaio, Ana D. (2021)
Quarrying activities cause profound modifications on ecosystems, such as removal of vegetation cover, biodiversity loss and depletion of ecosystem services. Ecological restoration stands as a solution to revert such effects. Concomitantly, awareness is currently being given on ecosystem services and ecological processes to evaluate restoration efficiency. The objective of the study was to assess restoration success in a quarry subjected to restoration practices for the last 40 years involving the plantation of native Mediterranean vegetation and the non-native Aleppo pine Pinus halepensis. The study was carried out by assessing the effectiveness of seed dispersal service provided by birds in the restored quarry by comparing this service to neighbouring natural (shrubland) and other semi-natural areas (oak-pine mixed open and Aleppo pine forest) present at the landscape. For this purpose, we explored bird composition structure and seed dispersal networks using point counts and faecal samples of mist-netted birds. We also collected vegetation structure data and explored its effect on bird community composition. Our results showed that bird abundance in the restored quarry was significantly lower, and its bird community was compositionally different than natural shrubland and semi-natural areas. For instance, seed-dispersing birds, woody and shrub/ground foragers and partially migrators were the most affected groups at the restored area. Bird community composition and their traits were likely driven by vegetation characteristics, with higher native vegetation cover and fruit richness promoting higher bird abundance and Aleppo pine cover negatively influencing seed-dispersing birds. Concurrently, seed dispersal network in the restored quarry was less complex than in other areas. Seed dispersal services in the restored quarry were below the reported values for neighbouring natural and semi-natural areas and are likely driven by the low abundance of seed-dispersing birds. We consider that the causes affecting this group's low abundance can be related to revegetation measures favouring Aleppo pine, combined with a shallow soil depth and poor soil quality, which may have constrained native vegetation development. We conclude that seed dispersal services at the quarry are depleted, which may suggest a low restoration success concerning ecosystem functioning. Our results strengthen that quarry revegetation with non-native species must be avoided, since it alters bird community composition, and consequently, affects seed dispersal service provided by birds.